2022
DOI: 10.1155/2022/7968999
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Observation of Laser Peripheral Iridoplasty with Number of Laser Shots in the Treatment of Acute Angle-Closure Glaucoma

Abstract: Objective. To quantitatively study the intraocular pressure (IOP) control and chamber angle opening degree of patients with acute angle-closure glaucoma (stage of attack) treated by laser peripheral iridoplasty (LPIP) with different numbers of laser shots, and to evaluate the efficacy and safety of different numbers of laser shots. Methods. Fifty-five patients (60 eyes) with acute angle-closure glaucoma treated in our hospital from May 2019 to December 2020 were selected as the research subjects. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%